Edible Film Based on Arrowroot Starch and Glycerol - Arifani, Erlina Nur; Tamalea, Rafi Renaldy (Journal of Agri-Food Science and Technology, 2024)
The edible film aims to improve the shelf life and safety of food by providing a physical barrier to external influences to prevent food deterioration. Arrowroot starch has high amylose content and excellent gelling ability, and it is massively produced in Indonesia. At the same time, glycerol has water-soluble and polar properties. So, studies were carried out on edible film based on arrowroot starch as the polysaccharide and glycerol as the plasticizer. This study was contributed to investigate the effect of the concentration of arrowroot starch (3, 4% w/v) and glycerol (1.25, 1.5, and 1.75% w/v) on physical properties (thickness by micrometer, functional group by FTIR, molecular structure surface by SEM) of edible film. The results showed that increasing the concentration of arrowroot starch and glycerol could increase tensile strength. Besides that, the formulations of 30% arrowroot starch with 12.5% glycerol and 40% arrowroot starch with 17.5% glycerol had the best tensile strength of 27.24 and 22.88 MPa, respectively. However, the results of the morphological analysis of the edible film on the arrowroot starch-glycerol formulation still contained pores and cracks.